2019
DOI: 10.1186/s12974-019-1600-7
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the microRNA signature of the peripheral sensory ganglia in experimental autoimmune encephalomyelitis (EAE)

Abstract: BackgroundMultiple sclerosis is an autoimmune disease with a distinct female bias, as well as a high prevalence of neuropathic pain in both sexes. The dorsal root ganglia (DRG) contain the primary sensory neurons that give rise to pain, and damage to these neurons may lead to neuropathic pain. Here, we investigate the sex differences of the DRG transcriptome in a mouse model of MS.MethodsNext-generation sequencing was used to establish RNA and microRNA profiles from the DRG of mice with MOG35–55-induced EAE, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Studies have identified certain miRNAs with high abundance in MSCs-Exos that possess unique immunomodulatory effects and are involved in myelin damage and regeneration associated with MS. Examples include miR-122 ( 42 ), miR-21 ( 42 , 43 ), miR-146a ( 44 ), miR-24 ( 45 ), and miR-223 ( 45 , 46 ). To investigate the impact of HUMSCs-Exos on OPC differentiation and maturation, we performed transcriptome sequencing to identify DEGs between HUMSCs-Exos-treated OPCs and untreated OPCs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have identified certain miRNAs with high abundance in MSCs-Exos that possess unique immunomodulatory effects and are involved in myelin damage and regeneration associated with MS. Examples include miR-122 ( 42 ), miR-21 ( 42 , 43 ), miR-146a ( 44 ), miR-24 ( 45 ), and miR-223 ( 45 , 46 ). To investigate the impact of HUMSCs-Exos on OPC differentiation and maturation, we performed transcriptome sequencing to identify DEGs between HUMSCs-Exos-treated OPCs and untreated OPCs.…”
Section: Discussionmentioning
confidence: 99%
“…Our lab has shown previously that TNFα is increased peripherally in circulating immune cells in EAE 12 . To confirm this result in our current tissue set, we assessed TNFα levels in the male and female EAE DRG by polymerase chain reaction (PCR) using previously described methods 38 . We found TNFα mRNA is elevated in both sexes in EAE (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 77%
“…Overall, our work provide experimental evidence supporting the link between environmental modifications, behavioral changes and precise miRNAs profiles in the mouse PFC. Specific miRNA signatures have been consistently found in multiple brain conditions ( Belzeaux et al., 2018 ; Burns et al., 2018 ; Friedman et al., 2019 ; Leidinger et al., 2013 ), and their understanding and manipulation would be extremely useful for clinical purposes.…”
Section: Discussionmentioning
confidence: 99%